Penyuluhan DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) Obat Bagi Masyarakat Desa Bingkat Kecamatan Pegajahan - Muhammad Gunawan; Siti Aisyah Tanjung; Andilala; Rismawati; Salsabila Maydina; Selfi (STIKES Columbia Asia Medan, 2025)
DAGUSIBU is one of the efforts to improve public health that is organized through health service activities by pharmaceutical workers. Health services that can provide community pharmaceutical workers include providing information on the use and storage of pharmaceutical preparations and medical devices. The public needs to know the importance of drug management from when they get a prescription to when they throw it away if it is not needed. So that the impact of community errors cannot be prevented. The lack of public curiosity about this is very dangerous. They should not underestimate the procedures for drug management. Starting from when they first get a prescription from a doctor, to how to dispose of it if it can no longer be used. In fact, if we make a slight mistake in managing drugs, it will have fatal consequences for consumers of the drug. The results of the Dagusibu Drug Management counseling (Get, Use, Store, Throw Away) in Bingkat, Serdang Bedagai Regency can provide insight and education on drug management from when they get a prescription to when they throw it away if it is not needed. So that the impact of mistakes made by the Bingkat village community cannot be prevented. Participants can apply the knowledge they have gained in their family and community environments.